2003
DOI: 10.32609/0042-8736-2003-4-4-36
|View full text |Cite
|
Sign up to set email alerts
|

Economy Modernization and the System of Values

Abstract: The author on the example of the groups of countries (Western and Eastern Europe, Latin America and Eastern Asia) considers the connection of values and economic development. Spain has demonstrated serious advances in the system of values. The main factors are market reforms and democratization. Traditional Russian values seriously reflect relations of archaic society with agrarian-feudal economy and hierarchical structure of authorities. The Soviet system of values looked like a traditional one in many ways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…7 They found that capitalist formal institutions are incompatible with post-communist informal norms because of the countries' historical experience with democracy and free markets. 8 Moreover, what we consider crucial in terms of our findings is that many transition economies appear to be locked in an institutional trap, that is, any institutional improvement is only associated with considerable economic and social losses, as the political sector is not independent enough from the economic sector. 9 Our findings verify the abovementioned views.…”
Section: Introductionmentioning
confidence: 83%
“…7 They found that capitalist formal institutions are incompatible with post-communist informal norms because of the countries' historical experience with democracy and free markets. 8 Moreover, what we consider crucial in terms of our findings is that many transition economies appear to be locked in an institutional trap, that is, any institutional improvement is only associated with considerable economic and social losses, as the political sector is not independent enough from the economic sector. 9 Our findings verify the abovementioned views.…”
Section: Introductionmentioning
confidence: 83%
“…The influence of culture on economic development is being actively studied. Thus, a group of Russian researchers came to the conclusion that Russian culture is a brake on the country's economic development (Kostina, 2015;Lebedeva & Yasin, 2009;Yasin, 2003Yasin, , 2007. These studies are supported by some empirical studies (Franke et al, 1991;Halkos & Tzeremes, 2013;Khan & Cox, 2017;Shane, 1993; van Everdingen & Waarts, 2003) In these studies, there is an elementary violation of logic: if culture and laws are not correspond to each other and slow down economic development, then the researchers suddenly decided that it is easier to change the culture.…”
Section: Introductionmentioning
confidence: 99%